Operational efficiency of Social Islami Bank Limited and a study of their Pre-pandemic and pandemic periods performances - Khaleed, Md. Imtiaz (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.